Development of a mathematical model for analyzing the perturbed state of a thermal power hydraulic system - Sazonova Svetlana; Shcherbakova Irina; Akamsina Nadezhda; Mozgovoy Nikolai; Sokolova Olga (E3S Web of Conferences, 2024)
The results of developing a model for analyzing the perturbed state of a thermal power hydraulic system are presented using the example of a heat supply system. The parameters of the operating mode of the thermal power hydraulic system were assessed after exposure to disturbing factors. It is noted that the choice of boundary conditions must be carried out taking into account the use of energy equivalence when analyzing the perturbed state of the investigated fragment of the hydraulic system. The developed model of steady flow distribution with non-isothermal flow of a viscous medium is presented. It is concluded that the developed mathematical model represents a qualitatively new approach to formalizing problems of flow distribution analysis in systems with adjustable parameters. The model can be considered as a generalized form of representing particular models of flow distribution when describing the object under study, which can be considered as a hydraulic circuit with adjustable parameters for nonisothermal flow of a viscous medium. It is shown that this model can be used to analyze and describe the flows and properties of a viscous medium in systems where it is possible to regulate parameters and non-isothermal flow is taken into account.